2017
DOI: 10.1521/aeap.2017.29.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Chosen by YMSM During Goal Setting to Reduce Risk for HIV and Other Sexually Transmitted Infections: Results From the Keep It Up! 2.0 Prevention Trial

Abstract: Although there have been great advances in the prevention of HIV in the last two decades, young men who have sex with men (YMSM) continue to be disproportionately impacted. Utilizing qualitative data from a sample of YMSM (N = 292) engaged in a randomized controlled trial testing the efficacy of an internet-based HIV prevention program, we examined YMSM’s goals for sexual risk reduction. Goals tended to focus on strategies used to prepare for safer sex or strategies to be used during sex. In both areas, five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Keep it up! [ 32 - 34 ] is a 7-module, multi-method intervention (one that includes the use of >1 method of data collection in a study) aimed at improving STI prevention strategies among young MSM in the United States. The main gaming component is called The Club Game.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Keep it up! [ 32 - 34 ] is a 7-module, multi-method intervention (one that includes the use of >1 method of data collection in a study) aimed at improving STI prevention strategies among young MSM in the United States. The main gaming component is called The Club Game.…”
Section: Resultsmentioning
confidence: 99%
“…First, there were those that were based in an educational institution (high school or university), included people of all genders and sexual orientations, and focused on contraception and STIs [ 27 - 29 , 41 , 42 ]. The second group was most commonly recruited from youth centers or sexual health clinics, focused exclusively on MSM, and had a clear focus on STI prevention and management [ 30 , 32 , 34 , 35 , 37 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2.0ʺ prevention trial demonstrated that young men who have sex with men (YMSM) engaged in goal setting as part of their HIV prevention efforts, focusing on strategies for safer sex. This approach allowed participants to create realistic and practical plans for HIV prevention, emphasizing the importance of setting specific, achievable goals for promoting safer sexual behaviors [11].…”
Section: Mean Difference Of Knowledge Subjective Norm Attitude and Be...mentioning
confidence: 99%